Comparative analysis of PWM techniques for Photovoltaic application with HERIC inverter - A, Karthikeyan; V, Thiyagarajan; P, Somasundaram (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Photovoltaic inverters achieves an effective and efficient system and plays an important role in reducing the total cost of the system. The main objective Â of this paper is to develope mathematical model and analyse the performance of photovoltaic fed Â HERIC inverter for different Pulse-Width Modulation (PWM) techniques. The two different carrier signals such as sinusoidal carrier signal and triangular carrier signals are used. The required PWM pulses are generated by comparing the trapezoidal reference signal with those carrier signals. The simulation is carried out using MATLAB/Simulink. The performance indices used in this comparison are THD, output power, fundamental output voltage and RMS value of output voltage.